Purwoceng (Pimpinella pruatjan Molk.) nanosuspension repairs spatial white albino wistar strains’ spatial memory degeneration after sleep deprivation - Rangga Wisnu Wardana; Tuti Sri Suhesti; Fitranto Arjadi (Biogenesis: Jurnal Ilmiah Biologi, 2022)
.